On Generalize Some Weak Forms of Supra Mappings in Intuitionistic Topological Spaces - Samer, R .Yaseen; Hind, F. Abbas (Tikrit Journal of Pure Science, 2023)
The aim of this paper is to introduce a new classes of supra mapping called Intuitionistic